Food Estate Management as Global Food Crisis Prevention Through the Implementation of the BNI Tani Card Program at Pulang Pisau - Abiwodo Abiwodo; Dhany Marlen (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Needs realization of the food estate concept partially in strengthening food security in the agricultural sector cannot be done by the government and society, but also involves corporations. One form of corporate involvement in this research is a program from BNI in the form of farmer cards. The farmer card program is expected to provide efficiency for farmers so that they can receive the distribution of government support in the right amount, the right type, the right time, the right place, the right quality and the right price. This study aims to measure the implementation of the BNI farmer card implementation to provide a pattern of relationship to the potential development of the food estate concept in Pulang Pisau. implementation of BNI farmer cards in the Pulang Pisau community through indicators of understanding and compliance (X1), behavior and culture (X2), economic conditions (X3), policy issues (X4), facilities and infrastructure (X5), and stakeholder support (X6) for Realization food estate concept. The research design was carried out in a cross-sectional manner using a quantitative approach through smart PLS. The results show the value of the six factors measured through the implementation of the BNI farmer card, which later on this value will become a basis for sustainability and policy adjustments in the realization of food estate in the region itself through government, community and corporate cooperation in realizing food security against global food crisis.